PRELIMINARY STUDY OF FISH OIL FROM MILKFISH SATAY BY PRODUCT USING DRY RENDERING EXTRACTION - Hanifah Fitriani; Aris Munandar; Dini Surilayani; Sakinah Haryati; Ginanjar Pratama; Bhatara Ayi Meata; Afifah Nurazizatul Hasanah; Rifki Prayoga Aditia (University of Sultan Ageng Tirtayasa, 2021)
Milkfish satay processing has been left viscera waste that may causes environmental pollution. The viscera waste has contained omega-3 which can be extracted as fish oil. Dry rendering is a method of fish oil extracting using temperature without water addition. The temperature of extraction greatly affects to quality of fish oil. The purpose of this study was to determine the optimal temperature of extraction and characterized fish oil quality extracted from milkfish viscera. This study used dry rendering extraction methode with three different temperatures (40ºC, 50ºC, and 60ºC) and tested the yield, free fatty acids, peroxide value, p-anisidine and total oxidation, for the best fish oil will be tested for its fatty acid profile. The best treatment for extracting fish oil from milkfish viscera used extraction temperature of 50ºC with yield (6.88%), free fatty acid (4.89%) peroxide value (29.35 mEq/kg), anisidine value (4.61 mEq/kg), and total oxidation (63.53 mEq/kg). The fatty acid profile of fish oil was dominated by palmitic acid (31.17%) and also contains omega-3 such as linoleic acid, docosahexaenoate acid (DHA), and eicosapentaenoate acid (EPA).